The Starunia collections in the Institute of Systematics and Evolution of Animals, Polish Academy of Sciences in Kraków - Kubiak, Henryk (Geotourism/Geoturystyka, 2025)
In the Institute of Systematics and Evolution of Animals of the Polish Academy of Sciences in Kraków there is a collection of remains connected with the discovery of the famous Pleistocene rhinoceros Coelodonta antiquitatis (Blum.), the so-called “second rhinoceros” of Starunia which has been World’s only nearly completely preserved fossil woolly rhinoceros so far. The carcass of that rhino was found in October 1929, i.e. 80 years ago in a shaft of an ozokerite mine near the village Starunia (the Eastern Carpathian Mts.) together with parts of skeletons of two other (“third” and “ fourth”) woolly rhinoceroses. Those finds were the results of an Expedition of the Polish Academy of Arts and Sciences. Beside the rhinoceroses abundant remains of flora and fauna, especially insects, were encountered in this locality.